Effect of cotrimoxazole on mortality in HIV-infected adults on antiretroviral therapy: a systematic review and meta-analysis - Amitabh B Suthar; Reuben Granich; Jonathan Mermin; Annelies Van Rie (The World Health Organization, 2012)
OBJECTIVE: To determine whether cotrimoxazole reduces mortality in adults receiving antiretroviral therapy (ART) for human immunodeficiency virus (HIV) infection in low- and middle-income countries through a systematic review and meta-analysis. METHODS: PubMed and Embase were searched for randomized controlled trials and prospective and retrospective cohort studies that compared mortality or morbidity in HIV-infected individuals aged > 13 years on cotrimoxazole and ART and on ART alone. The Newcastle- Ottawa Quality Assessment Scale was used to assess selection, confounding and measurement bias. Publication bias was assessed using Egger's and Begg's tests. Sensitivity analysis was performed because the I-squared statistic indicated substantial heterogeneity in study results. A random-effects model was used for meta-analysis. FINDINGS: Nine studies were included. Begg and Egger P-values for the seven that reported the effect of cotrimoxazole on mortality were 0.29 and 0.49, respectively, suggesting no publication bias. The I-squared statistic was 93.2%, indicating high heterogeneity in study results. The sensitivity analysis showed that neither the follow-up duration nor the percentage of individuals with World Health Organization stage 3 or 4 HIV disease at baseline explained the heterogeneity. The summary estimate of the effect of cotrimoxazole on the incidence rate of death was 0.42 (95% confidence interval: 0.29-0.61). Since most studies followed participants for less than 1 year, it was not possible to determine whether cotrimoxazole can be stopped safely after ART-induced immune reconstitution. CONCLUSION: Cotrimoxazole significantly increased survival in HIV-infected adults on ART. Further research is needed to determine the optimum duration of cotrimoxazole treatment in these patients.